HIPNOTERAPI DALAM KIDUNG RUMEKSO ING WENGI SUNAN KALIJAGA (KAJIAN HERMENEUTIK SCHLEIERMACHER) - Fenny Mahdaniar (QAULAN: Journal of Islamic Communication, 2025)
One of Sunan Kalijaga's da'wah media is Kidung Rumeksa Ing Wengi. This kidung is among the most influential and widely embraced forms of da'wah in Javanese culture. Many studies have explored da'wah messages in this kidung, but none have examined its meaning through a deeply hermeneutic lens. This study aims to holistically interpret Kidung Rumeksa Ing Wengi using Schleiermacher's hermeneutic approach and relate it to the concept of hypnotherapy. This research employs the library research method, incorporating Schleiermacher’s hermeneutic approach (grammatical and psychological interpretation), and integrates it with hypnotherapy theory in psychology. These research findings reveal that Kidung Rumeksa Ing Wengi served as a form of subconscious therapy for mad’uw (the audience of da’wah) within the Javanese kejawen community during Sunan Kalijaga's era. This subconscious psychological therapy aimed to build positive suggestions, helping the mad’uw overcome fears of disasters and mystical threats, which were often believed to be sent by opponents of Islam at the time. Through this kidung, Sunan Kalijaga sought to reinforce the belief that no calamity can befall anyone without Allah's permission.